Investment portfolio optimization using genetic algorithm / Mohd Fikri Hafifi Yusof - Yusof, Mohd Fikri Hafifi (Faculty of Computer and Mathematical Sciences, 2007)
Genetic Algorithm (GA) is adaptive methods which may be used to solve search and optimization problems. In investment, GA is helpful to find the best portfolio optimization. The five syariah securities are taken to optimize the portfolio and then find the best portfolio using the GA. All of the five securities are approved by Security Commission (SC) of Malaysia. The weekly return of each Syariah securities are taken from Stock Performance Guide Malaysia produced by Dynaquest Sdn. Bhd. The outcome from this project is the best syariah securities for we invest and get highest profit. Keywords: Genetic Algorithm, Portfolio Optimization, Investment